Social capital for whom? a case study of the implementation and practices of community-led enumerations in Stellenbosch Municipality 2011-2013 - Beukes, Anni Rosalen (Stellenbosch : Stellenbosch University, 2019)
Thesis (MA)--Stellenbosch University, 2019.